Complex association patterns for inflammatory mediators in induced sputum from subjects with asthma. Issue 7 (15th April 2018) - Hastie, A. T.; Steele, C.; Dunaway, C. W.; Moore, W. C.; Rector, B. M.; Ampleford, E.; Li, H.; Denlinger, L. C.; Jarjour, N.; Meyers, D. A.; Bleecker, E. R.; ,
Summary: Background: The release of various inflammatory mediators into the bronchial lumen is thought to reflect both the type and degree of airway inflammation, eosinophilic Th2, and Th9, or neutrophilic Th1, and Th17, in patients with asthma. Aims: We investigated whether cytokines and chemokines differed in sputum from subjects with more severe compared with milder asthma and whether unbiased factor analysis of cytokine and chemokine groupings indicates specific inflammatory pathways. Methods: Cell‐free supernatants from induced sputum were obtained from subjects with a broad range of asthma severity (n = 158) and assessed using Milliplex ® Cytokines/Chemokine kits I, II and III, measuring 75 individual proteins. Each cytokine, chemokine or growth factor concentration was examined for differences between asthma severity groups, for association with leucocyte counts, and by factor analysis. Results: Severe asthma subjects had 9 increased and 4 decreased proteins compared to mild asthma subjects and fewer differences compared to moderate asthma. Twenty‐six mediators were significantly associated with an increasing single leucocyte type: 16 with neutrophils (3 interleukins [IL], 3 CC chemokines, 4 CXC chemokines, 4 growth factors, TNF‐ α and CX3CL1/Fractalkine); 5 with lymphocytes (IL‐7, IL‐16, IL‐23, IFN‐α2 and CCL4/MIP1β); IL‐15 and CCL15/MIP1δ with macrophages; IL‐5 with eosinophils; and IL‐4 and TNFSF10/TRAIL with airway epithelial cells. Factor analysis grouped 43 cytokines, chemokines and growth factors which had no missing data onto the first 10 factors, containing mixes of Th1, Th2, Th9 and Th17 inflammatory and anti‐inflammatory proteins. Conclusions: Sputum cytokines, chemokines and growth factors were increased in severe asthma, primarily with increased neutrophils. Factor analysis identified complex inflammatory protein interactions, suggesting airway inflammation in asthma is characterized by overlapping immune pathways. Thus, focus on a single specific inflammatory mediator or pathway may limit understanding the complexity of inflammation underlying airway changes in asthma and selection of appropriate therapy.